Addressing the Stress of Work and Elder Caregiving of the Graying Workforce: The Moderating Effects of Financial Strain on the Relationship Between Work‐Caregiving Conflict and Psychological Well‐Being. Issue 5 (13th May 2014) - Kim, Najung; Gordon, Judith R.
<x xml:space="preserve">Abstract</x> Human resource policies and practices must consider the issues associated with an aging workforce, and, more specifically, the stress experienced by those involved in caring for elders. This study examined such stress by studying the relationship between work–elder caregiving conflict and well‐being, as well as the role of perceived financial need in moderating that relationship. The sample included 583 women who worked full‐time and had significant elder caregiving responsibilities. The analysis showed that work interfering with caregiving (WIC) was significantly associated with both positive and negative affect, but caregiving interfering with work (CIW) was not significantly associated with either. Perceived financial need decreased older women's psychological well‐being and moderated the relationship between work–elder caregiving conflict and psychological well‐being such that the negative effect of WIC was stronger for older women with higher perceived financial need, while CIW decreased the well‐being of older women with lower perceived financial need but not for those with higher need. The results stress the importance of considering elder care as a source of work‐family conflict when managing the aging workforce as well as suggest a way to attenuate the negative effect of work‐family conflict by managing the perception of financial resources and needs of the employees. © 2014 Wiley Periodicals, Inc.